Awareness of breast self-examination among undergraduate female nursing students / Nor Afefah Japar @ Jaafar, Nuratikah W. Mini and Siti Iqlima Shafiee - Japar @ Jaafar, Nor Afefah; W.Mini, Nuratikah; Shafiee, Siti Iqlima (2016)
Background: Breast cancer is the most common cause of cancer related death among women worldwide. One of the screening methods recommended by World Health Organization was breast self-examination. Breast self-examination (BSE) defines as self-generated, non-invasive and non-irradiative method of breast cancer detection. Objective: The study aimed to determine the level of knowledge attitude and practice on breast self-examination among female nursing students of Universiti Teknologi MARA (UiTM) Puncak Alam campus.